Fracture dislocations of Lisfranc's joint treated with closed reduction and percutaneous fixation - Perugia, Dario (Springer-Verlag, 2002)
We reviewed 42 patients (mean age 37.7±14.2 years) with closed fracture dislocations of Lisfranc's joint treated with percutaneous screw fixation. Mean follow-up was 58.4±17.3 months. The aim was to compare dislocations in which a perfect anatomical reduction had been reached with dislocations in which reduction was only near anatomical. The mean American Orthopaedic Foot and Ankle Society score for all patients was 81.0±13.5. There were no significant differences in outcome scores between patients with perfect anatomical reduction and patients with near anatomical reduction. However, patients with combined fracture dislocations obtained statistically better scores than patients with pure dislocations.